Correlations between ACE single nucleotide polymorphisms and prognosis of patients with septic shock. Issue 2 (28th April 2017) - Dou, Xin-Man; Cheng, Hui-Juan; Meng, Ling; Zhou, Lin-Lin; Ke, Yi-Hong; Liu, Li-Ping; Li, Yu-Min
Abstract : The aim of the present study is to investigate association between septic shock (SS) and angiotensin I-converting enzyme ( ACE ) single nucleotide polymorphisms (SNPs). From October 2009 to December 2016, 238 SS patients and 242 healthy individuals were selected for our study. ACE activity was detected, ACE rs4291 and rs4646994 polymorphisms were detected using PCR-restriction fragment length polymorphism (PCR-RFLP). The Kaplan–Meier survival curve was employed to evaluate the association between ACE SNPs and patients' survival and univariate and multivariate analyses to estimate risk factors for SS. ACE activity in the case group was increased in comparison with the control group. Allele and genotype frequencies of rs4291 and rs4646994 were different between the case and control groups. The TT genotype frequency of the rs4291 polymorphisms and the DD genotype of the rs4646994 polymorphisms of the case group were higher than those in the control group. The AT and TT genotypes indicated a significant elevation of ACE activity than the AA genotype, while a significant decline was found in the DI and II genotypes in comparison with the DI genotype. Patients with TT or DD genotypes had increased fatality rate within 7 and 30 days when compared with those with non-TT or non-DD genotypes. Lower sepsis-related organ failure assessment (SOFA) scores, rs4291, serum ACE and rs4646994 were all considered as risky factors for SS patients. The study demonstrates that TT genotype of rs4291 or DD genotype of rs4646994 may be indicative of a higher risk of SS and a poorer prognosis in SS patients.